1996
DOI: 10.1002/bjs.1800830319
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study of antibiotic prophylaxis for general and gynaecological surgery from a single centre in rural Africa

Abstract: In a district rural hospital in Uganda, 850 surgical patients were evaluated prospectively over a 3-year period to compare the clinical efficacy of conventional postoperative penicillin therapy with single-dose ampicillin prophylaxis for hernia repair and ectopic pregnancy, and with single-dose ampicillin-metronidazole prophylaxis for hysterectomy and caesarean section. The high rate of postoperative infection usually encountered in African hospitals after conventional treatment with penicillin for 7 days was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…The necessary basis for safe orthopedic surgery such as autoclaves, antiseptic wash, and prophylactic antibiotics has become available at most hospitals, even in the poorest countries, and hospitals that insert SIGN nails have motivated surgeons well-trained in the technique. This has been shown to be the case in general surgery in a large randomized study of prophylactic antibiotics use in Uganda, where the rate of infection after inguinal hernia repair dropped from 7.5% to 0% with correct antibiotic usage (Reggiori et al 1996). …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The necessary basis for safe orthopedic surgery such as autoclaves, antiseptic wash, and prophylactic antibiotics has become available at most hospitals, even in the poorest countries, and hospitals that insert SIGN nails have motivated surgeons well-trained in the technique. This has been shown to be the case in general surgery in a large randomized study of prophylactic antibiotics use in Uganda, where the rate of infection after inguinal hernia repair dropped from 7.5% to 0% with correct antibiotic usage (Reggiori et al 1996). …”
Section: Discussionmentioning
confidence: 93%
“…There have, however, been very few studies of good quality determining the infection rates after orthopedic surgery in low-income countries. Even though some authors have reported disturbingly high rates of postoperative infections in general and in gynecological surgery in LMICs (Reggiori et al 1996, Eriksen et al 2003), others have shown infection rates in orthopedic surgery matching those in high-income countries (Saris et al 2006, Gross et al 2010). …”
mentioning
confidence: 99%
“…Some investigators have reported that the administration of inadequate regimens increases the incidence of SSI and induces bacterial resistance [26,27]. Results from other resourcelimited settings provide evidence of potential efficacy of intervention to improve antibiotic usage [28,29]. Likewise, adoption of recommended hair removal methods should be considered [30,31].…”
Section: Discussionmentioning
confidence: 96%
“…No antibiotic prophylaxis was given after operation. This regimen has been proved effective for reducing the infectious morbidity rate in rural hospitals in developing countries [21].…”
Section: Preoperative Managementmentioning
confidence: 99%